Dynamic loads and thrust hysteresis of near-surface open propeller in regular head waves-an experimental study in a circulating water channel. (1st January 2021) - Zhang, Wencan; Ma, Ning; Gu, Xiechong; Feng, Peiyuan
Abstract: This paper investigates the dynamic load characteristics of a near-surface open propeller in regular head waves based on a model experiment in a circulating water channel, with the aid of captured free-surface profiles. The influences of periodical variation of submergence depth and inflow velocity on the dynamic load characteristics are systematically investigated, and the thrust hysteresis in periodical emergence condition is quantitatively evaluated. As conclusions, a critical instantaneous submergence depth is identified for this propeller in regular waves at a certain advance ratio; above this value, the dynamic load characteristics are not dominated by the propeller-surface interactions. For a periodically emerged propeller, the influence of the periodical variation of inflow velocity on the dynamic load characteristics is more significant as either submergence depth or wave height increases. With increasing wave period, the wave-caused load fluctuation amplitude increases in a more obvious manner in periodical emergence condition, but decreases less obviously in full submergence condition. Regarding the thrust hysteresis, it takes approximately 5 revolutions for this propeller in full submergence to regain full thrust. Lastly, the thrust fluctuation and loss due to slipstream inclination is considered responsible for thrust hysteresis, which happens as the previously emerged propeller heads into full submergence. Highlights: A systematical discussion of dynamic load in waves considering the periodical variation of submergence depth and inflow velocity. A high-resolution camera is used to capture the free-surface deformation and ventilation. A critical instantaneous submergence depth is identified at a certain advance ratio. A quantitative evaluation of the minimum revolutions in full submergence for this propeller to regain full thrust. Tip-vortex related ventilation due to upward slipstream inclination is considered as also responsible for the thrust hysteresis.